An Assessment of the Factors Affecting Economic Sustainability of State-Owned Enterprises: a developing Country’s perspective - Moono, Lweendo; Chisumbe, Sampa; Simushi, Sitwala; Aigbavboa, Clinton; Manda, Eneless (Journal of Economic Development, Environment and People, 2025)
The role of State Owned Enterprises (SOEs) is very important in the provision of basic services as well as social goods. However, despite their importance, most SOEs especially in developing countries are battling with heavy debt, failure to cover their operational costs and expenditure, thereby threatening their economic sustainability. This study sought to assess the factors that affect economic sustainability of state-owned enterprises in Zambia. The methodological approach adopted for this study was quantitative in nature with data collected from 100 employees sampled from SOEs as well as Zambia Development Agency (ZDA). Data collected was analysed using descriptive statistics as well as exploratory factor analysis. The findings revealed that , marketing (beta =.222, p-value of 0.032) and technology (beta = -.296, p-value of 0.004) have an effect on the economic sustainability of state owned enterprises. More so, the measurement items explaining each of the five variables were postulated. The study further found lack of funding, poor management practices, unfavourable government policies, market competition and unstable economic conditions to be the main challenges militating against sustainability of SOEs. The study therefore recommends promotion of partnerships between the SOEs and the private sector in technological innovation and adoption. Moreso, that for state owned enterprises to grow their customer base, there is need to develop competitive marketing strategies. This paper informs policy makers and bureaucrats on how to improve the productivity and profitability of state-owned enterprises.